Suicide Exposure in a Polymediated Age - Bell, Jo; Westoby, Christopher (Frontiers in Psychology, 2021)
With growing evidence that media plays a vital role in shaping public understanding of suicidality and influencing behaviours, media portrayals of suicidality have for some time been the focus of suicide prevention efforts. However, traditional media has changed, and now exists alongside an instantaneous interactive sharing of information created and controlled by anyone; the way most people use it today incorporates a wide variety of communication media. New Media, or Polymedia, describes media communication as both a product and process, where anyone can contribute and individuals can act as producers, consumers, audiences and critics. Thus in a ‘Polymediated age’, media exposure becomes much more complex. To understand how media exposure to suicide influences and impacts on others, it is important to take into account the communicative ecology of media technologies and the different interactions we can have with them. We researched the effects of this type of exposure by conducting in-depth interviews with individuals who have lived experience and knowledge of this phenomenon; this included individuals who are bereaved by suicide and professionals working across a range of post-suicide support services. In this paper we offer new insights into the scope, impact and influence of exposure to suicide via various interconnected communicative forms of media. In the age of New Media, news stories of suicide spread like wildfire with the potential to reach a global audience within days, or hours. By interacting with news information, individuals spread the story further by sharing it and generate content by commenting on it. The shared content of news stories and public comments which follow influence how suicidality and suicidal behaviours are perceived, transmitted and responded to. Our analysis reveals that exposure to and use of suicide-related content in this way can have both a positive and negative impact. We highlight important suggestions for those working in suicide prevention to develop media strategies that recognise the multiple ways in which users are exposed and impacted.